Child Costs and the Causal Effect of Fertility on Female Labor Supply: An investigation for Indonesia 1993-2008 - Jan Priebe (Georg-August-Universität Göttingen, Courant Research Centre - Poverty, Equity and Growth (CRC-PEG), 2010)
Over the last two decades Indonesia has experienced a signifcant decline in fertility rates and substantial increases in the level of education of women. Despite this development female labor force participation rates have remained roughly constant throughout this period. This paper explores the causes for the seeming unresponsiveness of female labor supply to changes in fertility. The empirical analysis is performed using annual data from the national household survey Susenas for the period 1993-2008. The final sample comprises about 850,000 woman aged 21 to 35 with at least two children. Identifcation of causal effects builds upon the empirical strategy as outlined in Angrist and Evans (1998). The results suggest that a considerable share of women in Indonesia works in the labor market in order to finance basic expenditures on their children. Therefore, reductions in fertility rates seem to have led to two opposing effects that contributed to aggregate levels of female labor supply being constant. While some women were more likely to participate in the labor market due to a lower number of children, others might now lack the need to engage in the labor market due to a relaxation in their budget constraint.
Keywords: C21; D01; J13; J20; 330; Causality; Child Costs; Indonesia; Labor Supply; LATE